RETHINKING TRAGIC HEROISM IN MODERN DRAMA: THE COMMON MAN TRAGEDY OF ARTHUR MILLER (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The article studies Arthur Miller’s groundbreaking idea of the tragic hero and the way he portrays the “common man,” a sort of man able to deliver profound tragedy. With a focus largely on Death of a Salesman, The Crucible and Miller’s essay Tragedy and the Common Man, it resists the Aristotelian vision limiting tragedy to nobility. These psychological, ethical, and social pressures placed on Willy Loman and John Proctor reveal in the process the manner that tragedy today finds expression from the everyday and social imperatives. This study focuses on the crucial process through which Miller democratised tragedy to deepen literary discussions about heroism in our era.